Tasaday scandal ; The lost tribe [videorecording] - Edwards, John; Taylor, Ian (Thames Production, 1987)
A story of the Tasaday scandal in Southern Mindanao and the claim of Manuel Elizalde, Jr. for discovering this tribal people who are really Manobos and T'bolis.